"It's a lesson with no correct answer": design issues in preservice teachers' use of history of science for lesson planning. Issue 3 (11th February 2023) - Park, Wonyong; Erduran, Sibel; Song, Jinwoong; Kim, Minchul
ABSTRACT: While many recent curriculum reforms recognise the value of history of science (HOS) in science teaching, in-depth investigations into teachers' experiences of planning HOS-based science lessons have been rare. We present a case study of two groups of preservice science teachers (PSTs) who collaboratively planned high school science lessons using HOS. The research aims were to understand what design issues arose and how they unfolded as each group planned the lesson. A design issue arises when group members dispute over a topic related to lesson planning and there is a need for decision making. We identified several major design issues around selecting a suitable history, adapting history, teaching a topic with no correct answer, balancing science and history, and empathising with people from the past, which manifested differently across the two groups . PSTs' reflections suggested that the collaborative planning experience helped them understand the limitations of content-focused pedagogical methods in planning HOS-based lessons and recognise various ways HOS can be used to enrich science teaching. The study sheds light on some challenges of planning an unfamiliar type of science lesson and how a collaborative planning experience can create opportunities to broaden PSTs' knowledge of science instruction.